ANALISIS RUMAH KABEL BAWAH TANAH PADA PROYEK PEKERJAAN JARINGAN UTILITAS SKTT 150 KV PLUMPANG - GAMBIR - Redaksi Tim Jurnal (FORUM MEKANIKA, 2017)
Underground cable distribution channels to be excellent especially in big cities like Jakarta. This is because the underground cable distribution is a solution to the difficulty of land acquisition that will be used for top cable networks. Nevertheless, there is an important factor to be considered in implementing the underground cable distribution channel that is the condition of the soil through which the cable. This study aims to determine the dimensions of the cable house was safe from the soil instability. The soil instability are the stability of bolsters and the shear stability and take into account the carrying capacity of the foundation used. The data used as a reference in the analysis using research data that has been done previously. In stability analysis and foundation bearing capacity used Geo5 software demo version aid. The results obtained from the analysis, with variations on the dimensions of the cable house used are 2 mx 2 m, 2.5 mx 2.5 m and 3 mx 3 m, it is seen that the greater the dimensions used then the security number of stability bolsters, soil shear stability and the carrying capacity of the foundation decreases. This is due to the greater the dimensions of the cable house used, the greater the burden borne by the soil.